Comorbidity of Urogynecological and Gastrointestinal Disorders in Female Patients With Lichen Sclerosus - Söderlund Jenni M; Hieta Niina K; Kurki Samu H; Orte Katri J; Polo-Kantola Päivi; Hietanen Sakari H; Haataja Marjut AM (Lippincott Williams & Wilkins, 2025)
OBJECTIVE
Lichen sclerosus (LS) is a chronic inflammatory disease with a significant impact on quality of life. The aim of this cross-sectional case-control study was to characterize concomitant urogynecological and gastrointestinal disorders in female patients with LS.
METHODS
A medical records search between 2004 and 2012 yielded 455 women and girls (mean age 64 years) with LS. The study cohort was compared with a 10-fold age- and sex-matched control cohort. Gynecological cancers and their precursors; gynecological, urinary, and gastrointestinal disorders; and pain syndromes were evaluated.
RESULTS
The well-known association between LS and increased risk of vulvar cancer and its precursors was also found in our study (relative risk [RR] = 100.0; p < .001 and high-grade squamous intraepithelial lesions RR = 110.0; p < .001, respectively), but we also found an increased risk for cervical cancer (RR = 6.0; p = .005) and endometrial cancer (RR = 2.9; p < .001). Gynecological pain syndromes such as dyspareunia (RR = 20.0; p < .001) and interstitial cystitis (RR = 5.0; p < .001) and urinary incontinence (RR = 4.8; p < .001) were also increased. Among gastrointestinal disorders, we found increased risk for celiac disease (RR = 6.8; p < .001), diverticular intestine diseases (RR = 1.9; p < .001), functional intestinal disorders (RR = 2.3; p = .003), and anal and rectal fissures (RR = 2.4; p = .046).
CONCLUSIONS
We found that female patients with LS have an increased risk for gynecological cancers as well as for several urogynecological and gastrointestinal disorders. Increased awareness is required to identify and treat these concomitant disorders.